The Interplay of Morality, Law, and Democratic Legitimacy in Habermas’s Political Philosophy (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This paper explores Jürgen Habermas’s discourse on the relationship between morality, law, and democratic legitimacy within modern societies. Habermas critiques Kantian and Rawlsian moral theories, advocating for a "dialogical" framework of practical reason. His work underscores the limitations of morality as a cohesive force in culturally diverse societies, and he proposes law, backed by political institutions, as a necessary complement to morality. In Between Facts and Norms, Habermas articulates the dual nature of law as both a fact and a norm, stressing that its legitimacy depends on rational discourse and public participation. This legitimacy rests on his discourse ethics, which integrates deliberative democracy with the legal system, emphasizing the democratic process as crucial for maintaining both private and public autonomy. The study sheds light on Habermas's nuanced approach to law as an instrument for social integration while affirming the role of morality in shaping democratic institutions